Treatment of Misophonia with Risperidone in a Patient with Autism Spectrum Disorder - Pan, Eric J.; Weleff, Jeremy; Anand, Akhil; Barnett, Brian S. (Case Reports in Psychiatry, 2022)
We report the case of a 32-year-old male with autism spectrum disorder (ASD) suffering from severe misophonia. After titrating risperidone to 2 mg twice a day, the patient reported a significant reduction in his symptoms and his Amsterdam misophonia scale-revised (AMISOS-R) score dropped by from 31 to 5. Upon discharge, the patient was noted to have decreased irritability and overall improved behavior and effect. This significant symptomatic improvement was likely not explained by inpatient admission alone or other simultaneous pharmacologic treatments, as the effect was seen during an isolated titration of risperidone with other treatments remaining constant. Although, unfortunately, follow-up findings indicated that the treatment was not curative for the patient, risperidone’s potential for treating misophonia may warrant systematic investigation.